DESIGN AND FABRICATION OF A SOLAR POWERED ROOF EXHAUST FAN - Nirmal, U.; Chan, W.T.; Lau, S.T.W.; Maratha, P. (Journal of Advanced Manufacturing Technology (JAMT), 2015)
In modern societies, every building should have a heating, ventilation and air conditioning (HVAC) system that provides sufficient comfort. However, the affordability and ease of installation of these systems vary widely. This research intends to design a solar powered roof exhaust fan with a simple installation design. The design has a structure such that parts are oriented around the axis of the fan. Two types of fans were tested: a centrifugal fan and an axial fan. In these experiments, parameters such as ambient, room and attic temperature were measured. The results showed that the centrifugal fan is more effective than the axial fan.